2018
DOI: 10.1002/cptc.201800130
|View full text |Cite
|
Sign up to set email alerts
|

Photofading of an Extended BOPHY Chromophore Dispersed in Poly(methyl methacrylate) as a Chemical Actinometer

Abstract: The target compound is a member of the symmetric pyrrole-BF 2 family, known as BOPHY, which has been equipped with 3,8styryl groups that push the absorption maximum to lower energy. To assist solubility and facile dispersion in plastic films, poly(ethylene glycol) chains are added to the styryl groups. The photophysical properties are somewhat sensitive to changes in solvent polarity and temperature due to the imposition of weak, intramolecular charge-transfer character. The chromophore bleaches under white-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Various substituents linked to the framework of the bispyrrole-boron were studied. [197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214][215][216] Although, most of the studies reported a six-membered ring formation, in 2016, Shen and co-workers reported 197 both five and six membered ring formation using hydrazine-Schiff base linked bispyrrole. Compound 217 (six-membered-ring) showed efficient solidstate fluorescence owing to the weak intermolecular interactions and a large Stokes shift, whereas, compound 218 (fivemembered-ring) has a small Stokes shift which results in weak fluorescence in the solid-state via self-quenching.…”
Section: Nn-chelate B-n Coordinated Compoundsmentioning
confidence: 99%
“…Various substituents linked to the framework of the bispyrrole-boron were studied. [197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214][215][216] Although, most of the studies reported a six-membered ring formation, in 2016, Shen and co-workers reported 197 both five and six membered ring formation using hydrazine-Schiff base linked bispyrrole. Compound 217 (six-membered-ring) showed efficient solidstate fluorescence owing to the weak intermolecular interactions and a large Stokes shift, whereas, compound 218 (fivemembered-ring) has a small Stokes shift which results in weak fluorescence in the solid-state via self-quenching.…”
Section: Nn-chelate B-n Coordinated Compoundsmentioning
confidence: 99%
“…Additional work has described the photochemical bleaching of BOPHY in liquid and solid phases. It appears that the compound is highly resistant to photofading under visible light illumination [12].…”
Section: Symmetrical Pyrrole-bf 2 (Bophy) Modulesmentioning
confidence: 99%
“…Such materials can provide strong absorbance from relatively narrow layers and are therefore highly attractive for applications as light harvesters. A further advantage of crystalline samples stems from their likelihood to display resistance toward photobleaching, a process that often plagues simple organic dyes in aerobic media. , Consequently, ever-increasing interest is focusing on the identification of fluorophores that retain characteristic emission in the crystalline phase without formation of H- or J-aggregates. In essence, there is a need for solid-state fluorophores exhibiting either broad emission spectra, such materials being putative white-light emitters, or narrow spectral profiles that could be useful as fluorescent markers .…”
Section: Introductionmentioning
confidence: 99%